(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Goganova A.V. Keywords: creativity of A. Platonov, Platonov’s novel ‘Tchevengur’, utopia. The novel ‘Tchevengur’ has been interpreted by scholars from different angles: social, philosophical, national eschatological and even as linguistic utopia. It is true that the novel combines different kinds of utopian consciousness. At the same time “Tchevengur” doesn’t represent the traditional utopia, thus it should be viewed as a unique literary work of the XXth century. The elements of utopia are only ‘the memory of a genre’ in it.